L’apport du Canada en matière de responsabilité internationale pour les dommages d’origine spatiale : l’Affaire du satellite Cosmos 954. - Farand, André (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
The nuclear satellite Cosmos 954 was launched by the Soviet Union in September 1977. Due to some difficulties in functioning, Cosmos 954 made an unscheduled return to earth and its debris scattered over a large portion of Canadian territory on January 24, 1978. The Canadian government, informed that the satellite had radioactive material on board, immediately began urgent operations to reduce the actual damage and to return the territory affected to its normal condition. Considering that the costs incurred during the operations should be claimed from the Soviet Union, the Government of Canada prepared a claim based in particular on the Convention on International Liability for Damage caused by space objects. The claim was presented to the Soviet representative on January 23, 1979.The Canadian government alleged that Canada sustained damage from the return on earth of the Cosmos 954 satellite. The Soviet Union, as the launching State, is absolutely responsible and should pay an appropriate amount of compensation. The amount claimed is slightly over 6 million dollars.Canada, subsequent to the incident, has proposed to the United Nations the adoption of a new regime for the use of nuclear energy in outer space.